Risk assessment in fall accidents at construction site - Bakeri, Mohamad Haniff; Che Ahmad, Asmalia; Abdul Tharim, Asniza Hamimi (2013)
Risk assessment is a subtopic from risk management. The main aim of risk assessment is to help all other management activities to reach the organization's aims directly and efficiently.Nowadays, occupational fatalities and injuries caused by fall accidents pose a serious problem in the construction project in the world.To develop the best development, many hazards and risk will be measured for success in the development project.Falls accident is a risk in development project especially in construction project.This problem must be study how to overcome or to reduce fall accidents at the construction project.The purpose of the study is about risk assessment on fall accidents at construction sites in Malaysia.The objectives of this research are to identify the types and causes of fall accidents at construction sites.To identify hazard related to fall accident.To develop a risk assessment matrix for fall accidents in construction sites, the secondary data is collected in the literature review from research paper from the internet database.Resides that, the data is also collected from web page and books.To get the primary data, the questionnaire will be used.Questionnaire form was the main source which contains various parts to achieve objective questionnaire survey will be made to experience parties in construction.The questionnaire is used to get the accurate data from the inspector, scaffolder, Project manager, safety officer, site supervisor, clerk of work, and workers in construction. The data collected will be compiled from the questionnaire feedback from the parties involved in construction site and composed in the form of diagrams, charts and tables or whichever method that is appropriate.To fulfill the requirement of collecting data,semi-structured interview will be use.The interview is conducted to asking the experience parties that involve in construction project about the related information of risk on fall accidents at construction sites.Based on that data collection, I will know the level of risk on fall accident.Besides that, I also will know why fall accident almost happens and how to prevent or reduce that risk.Based on this study performed I can make conclusion from that, the fall accident in construction project cannot decrease if the parties that have a responsibility not play their role.